Do therapist effects determine outcome in patients with shoulder pain in a primary care physiotherapy setting?. Issue Volume 107:Issue (2020) (June 2020) - Kooijman, Margit K.; Buining, Elisah M.; Swinkels, Ilse C.S.; Koes, Bart W.; Veenhof, Cindy
Abstract: Objectives: To explore whether a therapist effect exists in physiotherapists treating patients with shoulder pain and to identify if personality traits of the physiotherapist influences patients outcome. Design: Observational cohort study. Setting: Primary care physiotherapy practices. Participants: Data on patients with shoulder complaints that started and finished treatment between 2009 and 2012 were derived from the NIVEL Primary Care Database. Personality traits of the physiotherapist were identified using the Big Five Inventory. Data of 2814 patients and 56 physiotherapists were analysed using multi level linear regression. Main outcome measure: Severity of complaint was measured on a 10-point Likert scale at the start and end of treatment. Change score is used as outcome. Results: A therapist effect exists in the rehabilitation of patients with shoulder complaints in a physiotherapy setting; the physiotherapist explained 12% of variance and the personality trait extraversion showed a significant association ( P = 0.03) with change in treatment outcome. Conclusion: Current explorative study suggests that patients who were treated by therapists that tend to be more outgoing and energetic achieved better treatment results. Additional studies are needed to unravel the interplay between personality traits and other variables of importance, like patients' personality traits or psychological factors, in treating patients with shoulder complaints.